Nigeria Agricultural Insurance Scheme (NAIS): Prospect, Achievement and Problems - Aina O.S; Omonona B.T (Global Journal of Food and Agribusiness Management, 2021)
The place of agriculture in any society cannot be easily quantified given its importance in the life of human beings. Agriculture is expected to ensure adequate supply of food to the people, therefore, the need to set up food production to meet the ever increasing population in Nigeria. In 1960 and early 1970s, there was a growing dissatisfaction with the econocratic perspective of development which places premium on economic indicators as economic growth rates and industrialization. Agriculture, unlike many other investment activities, is exposed to a wide variety of risks and uncertainties ranging from input supply and prices, agricultural yield, post harvest losses and product prices to the vagaries of nature such as inclement weather conditions, pests and diseases. Other natural hazards such as floods and fire outbreaks are equally important with regards to their impact on the success or failure of an agricultural enterprise. In order to boost agricultural production considerably, it is imperative to reduce the impact of these risks and uncertainties to the barest acceptable minimum. The need, therefore, for a mechanism that functions specifically, to keep the farmers in business cannot, be over emphasized, and hence, the need for an agricultural insurance scheme in Nigeria. Natural disaster as floods and droughts are beyond the control of borrowers and the lending institution. These risks and other which include fire out breaks are transferred to insurance companies. In Nigeria there is National Agricultural Insurance Company (NAIC), operating in Nigeria since 1987, with the main objective of protecting the farmers from devastating effects of natural disasters and to ensure payment of appropriate compensation sufficient to keep the farmers in business after suffering a loss. This has lead to increase in agricultural production level in the country. This paper tries to examine the prospects, achievement and problems of Nigeria Agricultural Insurance Scheme/Company (NAIS/NAIC).